Effects of production conditions on yield and surface area of activated carbon derived from sugarcane bagasse - S. R. M. Kutty, Kutty (2018)

(untitled)
Activated carbon is the bio-solid material produced by pyrolysis. The activated carbon properties are controlled by feedstock and pyrolysis variables. In this study, the impacts of these production variables on the yield and surface area of sugarcane bagasse derived activated carbon (SCBA) were investigated. Physicochemical properties of the produced activated carbon (AC) including pH, moisture content, fixed carbon, volatile matter and ash content were also investigated. X-ray fluorescence spectrometry (XRF), Fourier-transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM) were evaluated as SCBA properties determining its sorption potential. The SCBA was produced at temperature range of 500 to 900°C, heating rate of 10 to 20°C/min and residence time of 1 to 3 h. The pyrolysis conditions were optimized using response surface methodology (RSM) technique to maximize the values of the responses. Analysis of variance (ANOVA) of the results demonstrated that the data fitted well to the linear and quadratic equations.